Desaturation and heme elevation during COVID-19 infection: a potential prognostic factor of heme oxygenase-1 (2020)
Increased heme levels, anemia, and desaturation occur during infection. We aimed to compare the levels of heme, heme oxygenase-1 (HO-1), ferritin, and bilirubin in coronavirus disease 2019 (COVID-19) patients at different saturation levels. Heme and HO-1 enzyme levels significantly increased in the low SpO2 group, but further studies are required.